A dynamic model for rumors spread with communication costs - Accinelli , Elvio (2021)
In this article we start by reviewing some mathematical models for the spreadof rumors. We mention some studies carried out using graphs, stochastic andprobabilistic models and also some epidemic like and evolutionary models.We analyze a repeated game with the replicator dynamics for the spread ofa rumor in a society conformed by an informed population about a rumorthat communicates the rumor to another population. The rumor can becommunicated in its original form or with the opposite content. We comparethe results obtained when only social costs are involved with the case whenalso communication costs are present.